SPE Offshore Europe Oil and Gas Conference and Exhibition 2007
DOI: 10.2118/109072-ms
|View full text |Cite
|
Sign up to set email alerts
|

BP Norway: Zonal Isolation in Openhole Chalk Formation

Abstract: The Valhall field has been producing oil for 25 years. The completion strategy of the field has continuously been developed over the years, with cased hole completions with multiple propped fractures as main completion strategy since the mid 1990s. This completion technique was also chosen for the Valhall Flank Project initiated in 2001. The later stages of the project several of the well targets were located on the borders of the field, where the reservoir formation is considerably thinner and has a lower por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is suggested that using swelling packers can replace cementing and provide better zonal isolation (Kennedy et al 2005;Jorgensen et al 2007). Using swelling packers with a preperforated liner solves this problem.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that using swelling packers can replace cementing and provide better zonal isolation (Kennedy et al 2005;Jorgensen et al 2007). Using swelling packers with a preperforated liner solves this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Oil swelling elastomer will swell faster in lighter oils compared to heavier ones. 7,8 The objectives of the present study are to perform lab studies to: (1) Investigate oil swelling packers in different crude oils, (2) Examine the effect of oil gravity and viscosity on the performance of oil swelling packers, and (3) Assess the effect of HCl acids and brines on the swelled elastomers Common acid used in carbonate formations is HCl at various concentrations.…”
Section: Introductionmentioning
confidence: 99%